Congenital Haemangiopericytoma of the Chest Wall - Nabi, Uzma; Naseem, Nadia; Riaz, Sabiha (International Journal of Pathology, 2018)
Hemangiopericytoma is a rare vascular tumor that usually occurs in adults. The occurrenceof these tumors in infants, known as congenital or infantile hemangiopericytoma, is even rarer andtheir behavior may be more benign than the adult type. We describe a 10 days old male neonate withcongenital hemangiopericytoma, presenting with a mass on the right anterior chest wall at birth. Theanterior chest wall location is an unusual site for a congenital hemangiopericytoma. Tumor excisionwas performed and morphologic and immunohistochemical results confirmed the diagnosis of infantilehemangiopericytoma. There was no tumor recurrence during 11 months of follow-up.